The approach of value innovation towards superior performance, competitive advantage, and sustainable growth: A systematic literature review - Hajar, Mohammed A.; Alkahtani, Ammar Ahmed; Daing Mohd Nasir, Ibrahim; Mohd Ridzuan, Darun; Al-Sharaf, Mohammed A.; Tiong, Sieh Kiong (MDPI, 2021)
The value innovation strategy of pursuing differentiation and low cost has diverged and correlated with various notions and perspectives, which adds complexity and ambiguity to the current knowledge of value innovation. Thus, this study uses a systematic literature review methodology to identify key scientific contributions to the field of value innovation by providing a structured reliable overview of the current knowledge. This study aims to integrate the findings of previous research on value innovation to identify where conclusions converge and diverge and highlight emerging trends and gaps in the literature. This study seeks to answer the research question, “How can value innovation be an approach for superior performance, competitive advantage, or sustainable growth?” In this context, results are achieved through analyzing and synthesizing 73 empirical articles on value innovation literature published from 1997 to January 2021. Particularly, this study contributes to the extant literature by providing an integrative framework that summarizes the literature findings and addressing thematic classifications of the value innovation process. This study also helps further improve research on value innovation by identifying gaps and suggesting a conceptual model to mitigate those gaps.